THE EFFECT OF ROTOR ROTATION SPEED ON DECREASED LABORATORY LIQUID WASTE POLLUTING PARAMETERS - Muhammad Al Kholif; Joko Sutrisno; Indah Nurhayati; Retno Setianingrum (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
aboratory wastewater is produced through laboratory activities. Laboratory wastewater can have a large impact on the environment if it is not processed before being discharged into the water body. Laboratory waste treatment can be carried out using suspended growth technology to reduce pollutant loads, especially Biological Oxygen Demand (BOD5) and Chemical Oxygen Demand (COD). Aims: This study aims to treat wastewater produced by the activity of laboratory using suspended growth technology. Methodology and Results: This research was conducted by finding the most efficient rotor rotation in degrading the load of BOD5 and COD pollutants. The reactor used is a Mixed Flow Reactor type reactor made of acrylic material with a thickness of 5.5 mm. The reactor is arranged into three series with the same sampling time and different rotor turns that expressed in rotors per minute (rpm). The reactor series consists of Reactor I with 50 rpm rotor rotation speed, 100 rpm Reactor II and 150 rpm Reactor III. Processing is carried out using 8 hours of detention time and variation of sampling time every 8 hours. Conclusion, significant and impact study: From the results of the study obtained the highest level of effectiveness of reducing pollutant load on processing using 150 rpm rotor rotation and 40 hours sampling time which is 94.6% for BOD5 parameters and 94.4% for COD parameters.